Strategi Gerakan Mahasiswa Nasional Indonesia (GMNI) dalam Meningkatkan Kemampuan Leadership Mahasiswa di STIKES Hamzar - Ayatullah Ayatullah; Kamaruddin Kamaruddin; Randa Gusti Pradana; Supriadi Supriadi; Rian Hidayat (PALAPA, 2024)
Student organizations are an inseparable part of campus life and play an important role in developing students’ capacities, including leadership abilities. This study aims to examine the strategies used by the Gerakan Mahasiswa Nasional Indonesia (GMNI) to improve students’ leadership abilities in East Lombok. This study used a qualitative method, with data collected through interviews, observation, and documentation involving GMNI administrators and members in East Lombok. The results showed that GMNI implemented tiered cadre formation, regular training, and involvement in social activities as efforts to develop students’ leadership. However, the implementation of these strategies still faced several challenges, such as limited resources and low student interest. This study concludes that GMNI’s strategies are quite effective in improving students’ leadership abilities, but innovation and adaptation are still needed to make them more relevant to the conditions of students in the current digital era.